Thermodynamic studies on adsorption of BSA using nylon membrane: article - Roslan, Ahmad Muzakkir; Ideris, Norhidayah (2017)
The aim of the study was to investigate the nylon membrane morphology and thermodynamic aspects for adsorption of Bovine Serum Albumin (BSA) as model protein on a nylon membrane. The study focused on the nylon membrane morphology and the effect of temperature on BSA adsorption. The morphology has been studied by using scanning electron microscope (SEM), FTIR-ATR spectroscopy and contact angle analyzer whereas the thermodynamic would be using the dot blotting method. The findings of the studies show that the nylon membrane sample is moderately porous (46.72±0.018%), small pore size (0.159±0.039 µm, 0.181±0.039 µm) with hydrophilic (55.6°) nature that gave decent adsorption of BSA. While the thermodynamic study indicates that the adsorption reaction was exothermic (∆rHo -1.871 kJ/mol), the adsorption may be dominated by physical reaction. The distribution of BSA molecules on adsorbent is less chaotic than the BSA mixture (∆rSo -0.421 kJ/mol.K). In addition, the process is not spontaneous but feasible (∆rGo 126 kJ/mol.K). The findings from the adsorption of BSA may be used to evaluate the modification of nylon membrane needed to obtain optimum adsorption and as the basis for different membrane’s performance study in BSA adsorption